Stability analysis of Monkeypox virus transmission dynamics using the SEIVR approach - Setyowisnu, Glagah Eskacakra; Saputro, Isnu Aji; Fikri, Mohamad Izudin; Rahmawati, Rahayu Nur; Ramdhanu, Ade Bagus (Journal of Evidence-based Nursing and Public Health, 2025)
Backgorund: Monkeypox is a zoonotic infection caused by the monkeypox virus (MONKEYPOXV), which has the potential to be transmitted from animals to humans. This virus can be transmitted through direct contact with infected animals such as monkeys, rats, and squirrels. In 2023, the World Health Organization classified monkeypox as a global pandemic, prompting stricter prevention measures worldwide. Given the significant increase in the number of cases and the challenges in controlling the spread of the virus, this study aims to develop a SEIVR (Susceptible, Exposed, Infected, Vaccinated, Recovered) mathematical model that can describe the dynamics of the spread of the monkeypox virus in Indonesia. Methods: There are two cases of the SEIVR model that will be studied; those are disease-free and endemic cases. From the cases, the stability of the model will be found. The Routh-Hurwitz criterion will also be used to analyze the stability due to the complexity of the eigenvalues. Findings: In the study conducted, simulations indicated that the infected population would coexist or remain for a fairly long time. This phenomenon is caused by the stable nature of the model. The dynamics of the model can also be seen by considering the obtained reproductive number. Although the infected population persists for a long time, the numbers are quite low. Conclusion: Vaccination does not have a significant impact. Therefore, further research using a treatment compartment or virus transition in rodents needs to be conducted for further study. Novelty/Originality of this Article: The novelty of this research lies in the use of the SEIVR model to map the spread of monkeypox in Indonesia and analyze its stability using the Routh-Hurwitz criteria and numerical simulations. This approach provides an initial overview of case persistence and vaccination effectiveness.